Effectiveness of Providing Snakes and Ladders Game-Based Education to Mothers With Toddlers Regarding Stunting Prevention - Mona Isabella; Abi Muhlisin (Indonesian Journal of Global Health Research, 2026)
Stunting is a chronic nutritional problem that affects the growth and development of toddlers. Increasing mothers’ knowledge through interactive educational media is one of the prevention efforts. This study aims to determine the effectiveness of snakes and ladders game-based education on stunting prevention at the Lorog Tawangsari Posyandu. The method used was a quantitative descriptive case study with purposive sampling of 15 mothers with toddlers. Knowledge was measured using pre-test and post-test questionnaires. The results showed an increase in good knowledge from 13.3% to 80% and a decrease in poor knowledge from 66% to 0%. Snakes and ladders game-based education is effective in increasing maternal knowledge and can be used as an alternative health education method.